Comparison of translational momentum and mechanical energy produced by lower limb muscles between horizontal and vertical jumps - a computer simulation study - Suzuki, Y.; Murata, M. (International Journal of Sport & Health Science, 2020)
To jump higher or farther, it is important to control the direction of translational momentum without reducing the mechanical energy produced by lower limb muscles. The purpose of this study was to compare the translational momentum and mechanical energy produced by lower limb muscles between horizontal and vertical jumps. Horizontal and vertical squat jumps were simulated using a musculoskeletal system consisting of four rigid segments actuated by six muscles. The translational momenta and mechanical energies produced by the six muscles were calculated. The force development patterns of hamstrings and rectus femoris were different between the two jumps, although other muscles produced similar forces. The hamstrings produced more forward momentum in the horizontal jump, while the rectus femoris produced more backward momentum in the vertical jump. In addition, the work outputs of the six muscles were nearly equal between the two jumps. The hamstrings transferred mechanical energy from knee to hip, while the rectus femoris transferred it from hip to knee. These results suggest that the hamstrings and rectus femoris play an important role in controlling jumping direction without reducing the total amount of work outputs of lower limb muscles.